Effects of the small molecule SIRT1 activator, SRT2104 on arterial stiffness in otherwise healthy cigarette smokers and subjects with type 2 diabetes mellitus. Issue 1 (17th May 2016) - Venkatasubramanian, Sowmya; Noh, Radzi M; Daga, Shruti; Langrish, Jeremy P; Mills, Nicholas L; Waterhouse, Brian R; Hoffmann, Ethan; Jacobson, Eric W; Lang, Ninian N; Frier, Brian M; Newby, David E
Abstract : Objective: Arterial stiffness increases with age, and is associated with adverse cardiovascular outcome including increased mortality. The effect of the oral small molecule SIRT1 activator, SRT2104, on arterial stiffness was examined in otherwise healthy cigarette smokers and participants with type 2 diabetes mellitus. Methods: 24 otherwise healthy cigarette smokers and 15 people with stable type 2 diabetes were randomised in a double-blind placebo-controlled crossover trial and received 28 days of oral SRT2104 (2.0 g/day) or matched placebo. Blood pressure was measured using non-invasive oscillatory sphygmomanometry. Pulse wave analysis and velocity were measured using applanation tonometry at baseline and the end of each treatment period. Owing to the small sample size and similar trends for both groups, data for the two groups were pooled (post hoc analysis). Results: Compared to placebo, treatment with SRT2104 was associated with a significant reduction in augmentation pressure (p=0.0273) and a trend towards improvement in the augmentation index and corrected augmentation index (p>0.05 for both). However, no changes were observed in pulse wave velocity and time to wave reflection (p>0.05). Systolic and diastolic blood pressures remained unchanged throughout the study. Treatment by cohort interaction was not significant for any of the pulse wave parameters, suggesting that the response to SRT2104 in otherwise healthy smokers and people with diabetes was consistent. Conclusions: SRT2104 may improve measures of arterial stiffness in otherwise healthy cigarette smokers and in participants with type 2 diabetes. Definitive conclusions are not possible given the small sample size and exploratory nature of this analysis. Trial registration number: NCT01031108.